2015
DOI: 10.1002/hyp.10679
|View full text |Cite
|
Sign up to set email alerts
|

Using concurrent DNA tracer injections to infer glacial flow pathways

Abstract: Abstract:Catchment hydrology has become replete with flow pathway characterizations obtained via combinations of physical hydrologic measurements (e.g. streamflow hydrographs) and natural tracer signals (e.g. stable water isotopes and geochemistry). In this study, we explored how our understanding of hydrologic flow pathways can be improved and expanded in both space and time by the simultaneous application of engineered synthetic DNA tracers. In this study, we compared the advective-dispersive transport prope… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
52
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 44 publications
(52 citation statements)
references
References 84 publications
0
52
0
Order By: Relevance
“…Future research should aim at testing this hypothesis. Based on these results, future research in similar glacierized catchments should consider the following: The application of end member mixing analysis should account for the high spatial and temporal variability in the tracer signature of the water sources. Furthermore, some assumptions, such as the use of spring water as an end member (and proxy for groundwater) and the significant relation between elevation and isotopic composition of snow or glacier melt water, should be carefully checked. An isotope‐based two‐component hydrograph separation could be used to quantify the rain water fraction to stream runoff and to investigate the main hydrological mechanisms during rainfall–runoff events (Dahlke et al, ). Stream water EC dynamics could be analysed at the seasonal scale and during melt‐induced runoff events to assess temporal changes in glacier melt water contribution to stream runoff and to identify any hysteretic relations between streamflow and stream water EC (Engel et al, ; Zuecco, Penna, & Borga, ; Zuecco, Penna, Borga, & van Meerveld, ). Other tracers, such as major ions and trace elements, could be used to quantify the contribution of subglacial flow to stream runoff and perform a geographical source analysis (Rodriguez et al, ), or DNA injections could be applied to infer the main glacier flow pathways (Dahlke et al, ). …”
Section: Conclusion and Future Researchmentioning
confidence: 99%
See 1 more Smart Citation
“…Future research should aim at testing this hypothesis. Based on these results, future research in similar glacierized catchments should consider the following: The application of end member mixing analysis should account for the high spatial and temporal variability in the tracer signature of the water sources. Furthermore, some assumptions, such as the use of spring water as an end member (and proxy for groundwater) and the significant relation between elevation and isotopic composition of snow or glacier melt water, should be carefully checked. An isotope‐based two‐component hydrograph separation could be used to quantify the rain water fraction to stream runoff and to investigate the main hydrological mechanisms during rainfall–runoff events (Dahlke et al, ). Stream water EC dynamics could be analysed at the seasonal scale and during melt‐induced runoff events to assess temporal changes in glacier melt water contribution to stream runoff and to identify any hysteretic relations between streamflow and stream water EC (Engel et al, ; Zuecco, Penna, & Borga, ; Zuecco, Penna, Borga, & van Meerveld, ). Other tracers, such as major ions and trace elements, could be used to quantify the contribution of subglacial flow to stream runoff and perform a geographical source analysis (Rodriguez et al, ), or DNA injections could be applied to infer the main glacier flow pathways (Dahlke et al, ). …”
Section: Conclusion and Future Researchmentioning
confidence: 99%
“…• Other tracers, such as major ions and trace elements, could be used to quantify the contribution of subglacial flow to stream runoff and perform a geographical source analysis (Rodriguez et al, 2016), or DNA injections could be applied to infer the main glacier flow pathways (Dahlke et al, 2015).…”
Section: Conclusion and Future Researchmentioning
confidence: 99%
“…This has led to an increase in new modeling methods that seek to improve process understanding at the catchment scale (e.g., Harman 2015; Klaus et al 2015;van der Velde et al 2012). These new methods, in turn, push for new data to better characterize flow pathway activation under various conditions and across various geological settings (Birkel et al 2012;Dahlke et al 2015;Volkmann et al 2016). With regard to high-latitude, arctic, and subarctic systems, hydrological tracer-based and geochemical data are often limited in their spatiotemporal availability and coverage Lyon et al 2016).…”
Section: Introductionmentioning
confidence: 99%
“…The study shows that power law SAS functions prove a powerful tool to explain catchment-scale transport processes that also has potential in less intensively monitored sites.PUBLICATIONS hydrologic systems to reproduce both hydrograph and tracer information [e.g., Rinaldo et al, 2015]. Hence, it is not surprising that a variety of environmental and biological tracers [e.g., Dahlke et al, 2015;Klaus et al, 2015;Beyer et al, 2016] are used to track the movement of water, thus placing hydrologic transport at the interface between hydrology and biogeochemistry [Hrachowitz et al, 2016]. Recently, the characterization of hydrologic transport has also impacted plant physiology studies, as it has been experimentally shown that water transpired by the plants may be sampled from a pool that is different from that generating stream water in some environments [McDonnell, 2014;Evaristo et al, 2015].Since early formulations, travel time distributions have been extensively explored [see McGuire and McDonnell, 2006] and a new generation of theoretical transport models has been introduced in recent years [Botter et al, 2011;van der Velde et al, 2012;Harman, 2015], which focus on catchment-scale nonstationary transport.…”
mentioning
confidence: 99%
“…PUBLICATIONS hydrologic systems to reproduce both hydrograph and tracer information [e.g., Rinaldo et al, 2015]. Hence, it is not surprising that a variety of environmental and biological tracers [e.g., Dahlke et al, 2015;Klaus et al, 2015;Beyer et al, 2016] are used to track the movement of water, thus placing hydrologic transport at the interface between hydrology and biogeochemistry [Hrachowitz et al, 2016]. Recently, the characterization of hydrologic transport has also impacted plant physiology studies, as it has been experimentally shown that water transpired by the plants may be sampled from a pool that is different from that generating stream water in some environments [McDonnell, 2014;Evaristo et al, 2015].…”
mentioning
confidence: 99%